Web-Based Employee Attendance Information System: Sistem Informasi Absensi Karyawan Berbasis Web - Nugraha, Prasadhana Aditya; Astutik, Ika Ratna Indra (Universitas Muhammadiyah Sidoarjo, 2022)
Along with the times, where computers are no longer valuable, the integrity to maximize the use of computers is increasing. Almost all organizations and companies ranging from small to large scale have started using computers to support their operational activities. However, often many companies ignore or do not maximize the use of computers in their operations, Attendance information system can help companies in maximizing the use of computers. With web-based, the attendance information system becomes one of the company's strengths in managing existing human resources. The implementation can be simply recording employee data ranging from general data to specific data such as the absence of an employee from entering to leaving. Using this employee attendance information system can help companies, especially admins in terms of recording employee absent data and making employee attendance report data and providing information to employees.